Predictors of electoral participation: What motivates citizens of the Republic of Srpska? - Delić, Dragana; Momić, Dragan (Political Life, 2026)
The subject of this paper is the study of factors influencing the electoral participation of the citizens of the Republic of Srpska. Using survey data, the authors seek to identify the key predictors of electoral participation and determine to what extent the survey results align with the dominant theoretical models of voting behavior. The analysis established that the decisive factors influencing a voter’s decision to cast a ballot or abstain are the following: political cynicism, a sense of civic duty, perception of the importance of one’s vote, perception of election transparency, and social pressure. Party identification also proved to be highly significant. Citizens who express a high level of interest in political events are more likely to vote in elections. Those who demonstrate loyalty to a political party regularly participate in elections. Therefore, it is reasonable to discuss the electoral participation of the citizens of the Republic of Srpska in terms of the cognitive model of electoral participation, and particularly the party identification model, given that political interest and party identification have proven to be the most significant predictors of electoral participation.